Prospective evaluation of a pediatric urodynamics protocol before and after limiting urine cultures. Issue 2 (April 2023) - Shannon, Rachel; Meyer, Theresa; Saldano, Dawn Diaz; Beilke, Liza; Snow-Lisy, Devon C.; Patel, Sameer J.; Rosoklija, Ilina; Johnson, Emilie K.; Yerkes, Elizabeth B.
Summary: Purpose: While our institution has historically obtained a urine culture (UCx) from every child at the time of urodynamics (UDS), no consensus exists on UDS UCx utility, and practice varies widely. This study aims to prospectively study our symptomatic post-UDS UTI rate before and after implementing a targeted UCx protocol. Materials and methods: A 2-part prospective study of patients undergoing UDS at one pediatric hospital was undertaken, divided into Phase 1 (7/2016-6/2017) with routine UCx at the time of UDS and Phase 2 (7/2019-6/2020) after implementation of a protocol limiting UCx at the time of UDS to only a targeted subset of patients. The primary outcome was symptomatic post-UDS UTI, defined as positive UCx ≥10ˆ4 CFU/mL and fever ≥38.5 °C or new urinary symptoms within seven days of UDS. Results: A total of 1, 154 UDS were included: 553 in 483 unique patients during Phase 1 and 601 in 533 unique patients during Phase 2. Age, sex, race, ethnicity, and bladder management did not differ significantly between phases. All 553 UDS in Phase 1 had UCx at the time of UDS, compared to 34% (204/601) in Phase 2. The rate of positive UCx decreased from 39% in Phase 1–35% in Phase 2. Three patients developed symptomatic post-UDS UTI in each study period, resulting in a stable post-UDS UTI rate of 0.5% (3/553) in Phase 1 and 0.5% (3/601) in Phase 2. These patients varied in age, sex, UDS indication, and bladder management. Four of the six (67%) patients had positive UCx at the time of UDS, one had a negative UCx, and one had no UCx under the targeted UCx protocol. Predictors of symptomatic post-UDS UTI could not be evaluated. Discussion: In the largest prospective study to date, we found that symptomatic post-UDS UTI was <1% and that UCx at the time of UDS can safely be limited at our hospital. This reduction has important implications for cost containment and antibiotic stewardship. We will continue iterative modifications to our protocol, which may eventually include the elimination of UCx at the time of UDS in all groups. Conclusions: This 2-part prospective evaluation at one pediatric hospital determined that the symptomatic post-UDS UTI rate remained <1% with no identifiable predictors after limiting previously universal UCx at the time of UDS to only a targeted subset of patients. Summary Table Urine cultures during urodynamics and antibiotic treatment by protocol. Summary Table   Retrospective [11 ] Prospective: Phase 1 Prospective: Phase 2 Time period 1/2013–1/2015 7/2016–6/2017 7/2019–6/2020 UDS urine culture protocol No protocol, routine urine cultures UDS protocol with universal urine cultures UDS protocol with limited urine cultures Urine culture with UDS 993/1057 (94%) 553/553 (100%) 204/601 (34%) Positive culture 402/993 (40%) 218/553 (39%) 72/204 (35%) Received antibiotic treatment after UDS, either based on culture protocol or symptoms 23/1057 (2%) 44/553 (8%) 36/601 (6%) Symptomatic post-UDS UTI 15 (1.4%) 3 (0.5%) 3 (0.5%)